Lignin-derived Pt supported carbon (submicron)fiber electrocatalysts for alcohol electro-osidation. - García-Mateos, Francisco José; Cordero-Lanzac, Tomás; Berenguer-Betrián, Raúl; Morallón, Emilia; Cazorla-Amorós, Diego; Rodríguez-Mirasol, José; Cordero-Alcántara, Tomás (Elsevier, 2017)
Lignin fibers, with and without phosphorus, and loaded with platinum have been prepared in a single step by electrospinning of lignin/ethanol/phosphoric acid/platinum acetylacetonate precursor solutions. Thermochemical treatments have been carried out to obtain lignin-based carbon fiber electrocatalysts. The electrospun lignin fibers were thermostabilized in air and carbonized at 900 °C. The effect of phosphorus and platinum content on the porous texture, the surface chemistry and the oxidation/electro-oxidation resistance have been studied. Phosphorus-containing carbon fibers develop a higher surface area (c.a. 1200 m2 g−1), exhibit a lower Pt particle size (2.1 nm) and a better particle distribution than their counterpart without phosphorus (c.a. 750 m2 g−1 of surface area and 9.6 nm Pt particle size). It has been proved that phosphorus improves the oxidation and electro-oxidation resistance of the fibers, avoiding their oxidation during the preparation thermal stages and is responsible of the generation of a microporous material with an unusual wide operational potential window (1.9 V). An important Pt–P synergy has been observed in the oxygen transfer during the oxidation and electro-oxidation of the fibers. The obtained carbon fibers can act directly as electrodes without any binder or conductivity promoter. The fibers with platinum have shown outstanding catalyst performance in the electro-oxidation of methanol and ethanol.
Keywords: Platino; Acido fosfórico; Lignina; Electrodos de carbono; Binderless carbon electrode; Electrospun lignin fiber; Platinum; Phosphoric acid; Alcohol electrooxidation